Uzbekistan [videorecording] : Islamic repression (Australia : Chip Taylor Communications)
Uzbekistan's president, Islam Karimov, heads an authoritarian-style regime that is intolent of opposition groups. There are no avenues for protest and critics questions whether the repression has crushed revolutionary Islam, or helped create it.